2009
DOI: 10.1002/bsl.861
|View full text |Cite
|
Sign up to set email alerts
|

Emotional evidence and jurors' judgments: the promise of neuroscience for informing psychology and law

Abstract: This article is a review of psychological and neuroscience research addressing how juror decision making is influenced by emotion elicited from potentially disturbing evidence such as gruesome autopsy photographs, victim impact statements, and information about a defendant's tragic personal history presented as mitigating evidence. We review (a) converging evidence suggesting that the presence versus absence of such evidence results in more punitive juror judgments, (b) social cognition theories that provide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 69 publications
(134 reference statements)
2
40
0
Order By: Relevance
“…Research has also shown that victim impact testimony influenced mock jurors to give harsher sentences when the defendant was female (Forsterlee et al, 2004). Studies which have investigated the effect of victim impact testimony on sentencing decisions have also shown that exposure to such testimony increases individuals' negative emotions (Forsterlee et al, 2004;McGowan & Myers, 2004;Myers & Green, 2004;Salerno & Bottoms, 2009). For example, participants who heard victim impact testimony felt greater anger and vengefulness, and they imposed the death penalty more than participants who did not hear the testimony (Paternoster & Deise, 2011), while highly emotional testimony evoked more negative emotions than less emotional testimony or testimony without emotion (Myers et al, 2002).…”
Section: Emotional Evidencementioning
confidence: 96%
“…Research has also shown that victim impact testimony influenced mock jurors to give harsher sentences when the defendant was female (Forsterlee et al, 2004). Studies which have investigated the effect of victim impact testimony on sentencing decisions have also shown that exposure to such testimony increases individuals' negative emotions (Forsterlee et al, 2004;McGowan & Myers, 2004;Myers & Green, 2004;Salerno & Bottoms, 2009). For example, participants who heard victim impact testimony felt greater anger and vengefulness, and they imposed the death penalty more than participants who did not hear the testimony (Paternoster & Deise, 2011), while highly emotional testimony evoked more negative emotions than less emotional testimony or testimony without emotion (Myers et al, 2002).…”
Section: Emotional Evidencementioning
confidence: 96%
“…In addition, unlike most mock jurors, real jurors deliberate, which would be expected to dampen the effects of their emotions (but cf. Bandes & Blumenthal, 2012), and real jurors know that they will be at least somewhat accountable to one another during deliberations for the reasons behind their decisions (Salerno & Bottoms, 2009), which should further attenuate the impact of their emotions on those decisions (Lerner et al, 1998).…”
Section: How Large Are Emotional Effects On Judgment?mentioning
confidence: 99%
“…They are also frequently presented with emotionally arousing materials (e.g., witness or victim statements, crime scene photographs) that have the Third-party Interventions, Anger, Attention Focus 31 potential to carry over and bias subsequent judgments. While relatively few studies have addressed this question (e.g., Salerno & Bottoms, 2009), the current research has the potential to inform the legal system in understanding when and how incidental anger affects third-party punishment and compensation, and how to counter the effects of incidental anger (e.g., by modulating third parties' attention focus; Van Dillen et al, 2012).…”
Section: Implications and Limitationsmentioning
confidence: 99%